Perancangan dan Analisa Turbin Darrieus Tipe H untuk Pembangkit Listrik Tenaga Arus Air - Ibrahim Ibrahim; Ilham Maulana; Muhajirin Muhajirin; Iskandar Iskandar (Jurnal Teknik Mesin Unsyiah, 2014)
This research designed and analyzed the use of current energy by employing the Darrieus turbine type H. This turbine was tested in an irrigation located in Bukit Meusara, Aceh Besar. It has a dimension of 0,3 m x 0,3 m with a blade shaped of NACA 0015 and tested on a variation of water speed flow of 1,43 m/s, 1,91 m/s and 2,16 m/s. An experiment on the influence of angle of attack was also done on -50, 00, 50 and 100. The results showed that the angle maximum turn was 90 rpm with the water speed flow of 2,16 m/s at angle of attack of 50. The maximum power produced by the turbine was as substantial as 26% of efficiency.